KEBIJAKAN PEMERINTAH DALAM PENGELOLAAN SAMPAH DOMESTIK DI KABUPATEN BANTUL PROPINSI D.I. YOGYAKARTA - Fangga, Fangga; Mulasari, Surahma Asti (Jurnal Kesehatan Masyarakat, 2016)
ABSTRACT Background: Garbage is a result of human activity are discarded because it was not useful, so that not all solid objects that are not used and disposed of so- called junk. Waste Management had only understood by the public sector. Waste disposed by people considered to just be the governments job alone to handle. So that the waste problem has always been a difficult problem to overcome, if it is not the role of an active community and awareness of the community it self. It is known from the data monthly report garbage in the Department of the Environment and from interviews the researchers did in June 2012 at the Department of Public Works Bantul. Number of people who throw their garbage into the existing illegal TPSS Bantul cause existing waste management can not be performed optimally and more difficult to overcome the existing problems of garbage. Based on the background above, the researcher is interested in studying "Government Policy in the Domestic Waste Management In Bantul. Methods: The study was descriptive qualitative. Data obtained on the terms of the interview of Kapala UPT KP3 from DPU and Sub Sector and Sub-Sector Document LH Institutional Capacity of the Environment Agency. Instrument or tool used in this study is an interview guide. Descriptive data were analyzed qualitatively by telling the phenomena that occur and analyzed based on the data obtained from the field. Acquisition of legality or validity of the study the researchers did obtained by triangulation of data. Results: The regulation is used in the management of domestic waste in Bantul is RI Law No.18 of 2008, No.33 of 2010 Permendagri and Regional Regulation No. Bantul. 15 in 2011. Domestic waste management services in Bantul conducted by the Department of Public Works and BLH. Waste management program in Bantul conducted by two institutions: the BLH and Public Works Department. BLH tasked with the establishment of an independent institutional waste management, while DPU shall carry out the regional administration in the field of public works. Allocation of funds used in the management of domestic waste from DAK and budget. Incentives have been given oelh Bantul government to community groups play an active role in the management of domestic waste. Conclusion: Regulation is used in the management of domestic waste in Bantul is RI Law No.18 of 2008, No.33 Permendagri in 2010, and the Regional Regulation No. Bantul. 15 in 2011. The services provided by the government to the community in the management of domestic waste in Bantul going well. Program activities by the government in the management of domestic waste in Bantul going well. Allocation of funds used in the management of domestic waste in Bantul Rp. 541 969 150, -. Fund issued BLH of the total budget in 2012 amounted to Rp. 1924580640, -. Incentives are issued in domestic waste management in Bantul include: garbage bins, composter, sewing machine, wheelie bins, organic waste thrasher, thrasher plastic waste, and incorporating the parties / institutions that excel in waste management at the national level competition.